2017
DOI: 10.4103/1793-5482.180951
|View full text |Cite
|
Sign up to set email alerts
|

The minipterional approach for ruptured and unruptured anterior circulation aneurysms: Our initial experience

Abstract: Objective:To report our experience with the minipterional (MPT) craniotomy approach for anterior circulation aneurysms and to discuss the clinical outcomes as well as to evaluate the advantages of this unique approach.Materials and Methods:Single-center retrospective review of 57 cases involving anterior circulation aneurysms both ruptured and unruptured aneurysms treated with the MPT. We analyzed the clinical and patient demographic data, aneurysm characteristics, surgical outcomes, and complications in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…38 studies were found eligible for the established criteria (27 retrospective cohort studies, one outcome research, four prospective cohorts, one case–control, and five clinical trials). [ 1 , 5 - 8 , 10 , 11 , 13 , 17 , 18 , 20 , 21 , 23 - 25 , 28 - 31 , 33 , 34 , 36 - 38 , 41 , 44 , 45 , 48 ] 118 duplicates were found. 1328 papers were excluded as determined by the exclusion criteria [ Figure 1 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 studies were found eligible for the established criteria (27 retrospective cohort studies, one outcome research, four prospective cohorts, one case–control, and five clinical trials). [ 1 , 5 - 8 , 10 , 11 , 13 , 17 , 18 , 20 , 21 , 23 - 25 , 28 - 31 , 33 , 34 , 36 - 38 , 41 , 44 , 45 , 48 ] 118 duplicates were found. 1328 papers were excluded as determined by the exclusion criteria [ Figure 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pterional craniotomy (PC) is a classic approach for all anterior circulation aneurysms, suprasellar tumors (i.e., pituitary adenomas and craniopharyngiomas), and neurosurgeries where the opening of the Sylvian fissure is a crucial step. [ 1 ] Described for the 1 st time by Yasargil et al ., PC continues to be one of the most used nowadays. [ 2 , 46 ] PC has several variants such as the orbitozygomatic (OZ) approach, first proposed by Hakuba et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although there are studies that exclude ACoA aneurysms located in deep positions because they believe MPT to be unsuitable for these cases, 2) 6) we considered that MPT would need to be applicable even to ACoA aneurysms, which are known to be highly prevalent and to rupture even at small sizes. Therefore, we were able to successfully obliterate 154 cases with various directions, sizes, and locations.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports with MPT for anterior circulation aneurysms included relatively small volume less than 50 cases, 8) 22) 25) 27) and we think that the evaluation of clinical and functional results maybe not fully investigated. 2) 6) 11) 16) By the way, Rychen et al reported a systemic review of the literatures on minimally invasive alternative approaches to CPT, 21) and they collectively reviewed approach-related complications in a total of 22 MPT articles. Postoperative hematoma and infarction occurred in 2.2% and 3.1% of all patients, and wound infection and CSF leak was reported in 1.2% and 0.3%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation